2016
DOI: 10.1039/c5ee02843d
|View full text |Cite
|
Sign up to set email alerts
|

Capture of iodine and organic iodides using silica zeolites and the semiconductor behaviour of iodine in a silica zeolite

Abstract: During the reprocessing of spent nuclear fuel rods, a highly moist off-gas mixture containing various volatile radioactive species, such as iodine (I2), organic iodides and nitric acid, is produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(98 citation statements)
references
References 41 publications
0
98
0
Order By: Relevance
“…80 Besides metal cations, zeolites are also capable of adsorbing other radioactive molecules, such as iodine released during the dissolution of nuclear fuel rods. Recently, Pham et al 81 investigated the capture of iodine by using various types of porous materials, including all-silica zeolites, aluminosilicate zeolites, active carbons, and metal-organic frameworks. All-silica zeolites exhibited superior capability over other porous materials for I 2 removal from highly acidic dissolver solution.…”
Section: Water Purificationmentioning
confidence: 99%
“…80 Besides metal cations, zeolites are also capable of adsorbing other radioactive molecules, such as iodine released during the dissolution of nuclear fuel rods. Recently, Pham et al 81 investigated the capture of iodine by using various types of porous materials, including all-silica zeolites, aluminosilicate zeolites, active carbons, and metal-organic frameworks. All-silica zeolites exhibited superior capability over other porous materials for I 2 removal from highly acidic dissolver solution.…”
Section: Water Purificationmentioning
confidence: 99%
“…Technologically appealing properties may also appear if iodine is confined in zeolites, for example in the familiar silicalite (Figure ), where I 2 forms a semiconducting 3D‐supramolecular network (Figure ) . Indeed, the outstanding I 2 sorbent properties detected for this highly hydrophobic silicalite were ascribed to the scarcity of framework defects and the ability to tightly fit I 2 within the channels by forming a confined 3D‐network of iodine …”
Section: Organization Of Dihalogens In 1d Channelsmentioning
confidence: 99%
“…Section 5: confined water and water‐ion clusters is a topic of both historic and fundamental value (see Ref. [44, 45] for a review) – here, the focus is on water‐cation assemblies in natural zeolites. Section 6: confined halogen molecules in nanochannels form relatively simple composites, yet endowed with interesting properties, such as semiconductor behavior Section 7: organic chromophores encapsulated in nanosized containers show exceptional optical properties (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Samoć et al have recently demonstrated that formation of dye nanoaggregates, which can be also understood as molecular confinement, results not only in the growth of the emission intensity but also in sizable enhancement of the intrinsic two‐photon absorption cross‐section . It was also shown that the molecular iodine (I 2 ), confined in the zeolite channels, creates three‐dimensional supramolecular structures, which exhibit unique semiconductor properties . In recent years, much effort has been devoted to the studies of electric properties of spatially confined atomic and molecular systems.…”
Section: Introductionmentioning
confidence: 99%